STUDY OF BIOACTIVITY OF MELALEUCA ALTERNIFOLIA ESSENTIAL OIL IN CARIES REMISSION AND IT USE TO PROMOTE ORAL HEALTH - Silva, Wagner Alex de Medeiros; de Oliveira, Andréa Maria Brandão Mendes; Coelho, Luiz Fernando de Oliveira (ARACÊ, 2024)
The study aims to verify, measure and test the microbicidal efficacy of Melaleuca essential oil in vitro against the pathogen Streptococcus mutans (ATCC 25175). Methodologically, the study was experimental research, developed at MicroLAB/UFCG and BM-Biolam, evaluating the essential oil of Melaleuca alternifolia (melaleuca) against the pathogen already described in vitro in Muller-Hinton agar – AMH respectively, subjecting the samples to variation factors when incubated in a BOD type incubator at approximately 26±1°C. In all in vitro tests performed, a considerable increase in the Mean Halo Size – MHT was demonstrated with a concomitant reduction in the number of days for remission on the pathogen. Regarding the remissive effect (ERD) of the Probability of Survival – PS, percentage indices of PS at 50% (IC50) were obtained in SM-I of 25% (G), in SM-II of 21.4% (I) and in SM-III of 30% (K). At the 100% level (IC100) the average values increased in SM-I of 25% (H), in SM-II of 30% (J) and in SM-III of 50% (L). In this context, when evaluating the antibiograms against the taxon, it becomes viable to suggest the use of the essential oil – TTO in the preparation of dentifrices at the common concentration of [ssm]£120 mL×g-1 with D³54,4 mm, isolated or associated with FEC, and the value of [ssm] should be adjusted to each case.